The Gulf States threat perceptions and security policies - Shikārah, Aḥmad ʻAbd al-Razzāq (Emirates lecture series, 2007)
"Due to strategic, geopolitical and economic factors, outside observers regard the Gulf region as an area of vital interest. As such, threat perceptions relating to Gulf security have become increasingly salient not only for the Gulf states but for the international community as a whole. Indeed the "oil dimension" combined with the "geostrategic dimension" have shaped and framed the policies of many countries concerning the Gulf. In this context, the importance of curtailing and containing any threat that would endanger the overall security - particularly that of oil resources and supplies - of the region concerns outside powers. The main partners and players in the Gulf - the GCC states and the United States - must review any forthcoming proposal for the establishment of a new collective Gulf security system in order to be effective in revising current arrangements."--Publisher summary